A new hand dynamometer activforce isometric muscle activation on single joint muscle force of volleyball players - Yeliz Kahraman (Health Promotion & Physical Activity, 2023)
Isometric muscle activation of single joint to volleyball players is critic on sport performance to produce potential muscle force, however isometric measurement limited in isokinetic muscle activity measurement of volleyball players. Indeed, hand dynamometers commonly use in various body isometric force. Professional volleyball players age 16.23 ± 0.59 yr, body mass 60.22 ± 4.64 kg, hight 1.69 ± 0.04 m participated to peak and average isometric force measurement over 8 week pre and post test. Accordingly, single joint muscle force production measurement of volleyball players tested on isometric muscle activation using a new hand dynamometer activforce 2. Isometric muscle activation tests consisted of 24 body region from upper and lower compartment. For this isometric muscle action test detected on peak force outcomes (SEM: 37.90; CV: 1.79) and average force outcomes (SEM: 33.62; CV: 1.84). The high isometric muscle action joint loading performing mechanical test application recommended on athletic population to using isometric potential high contraction model by strength training performance separately in-season and off-season measurement modeling. Conclusion, peak and average force production progressive isometric modeling of volleyball athletes worked to current sport–health condition. As out, conclusion must be advanced isometric force measurement proper work in sport-specific tasks. The proper isometric force must be repeat sport performance outcome in different sport modalities.